Inovações pedagógicas em educação profissional: uma experiência de utilização do método de projetos na formação de competências - Barbosa, Eduardo Fernandes; Gontijo, Alberto de Figueiredo; Santos, Fernanda Fátima dos (Boletim Técnico do Senac, 2004)
This article presents an experience in professional education based on the application of the Projects Method as a pedagogical resource for developing competencies. This work has its origins in research on the curriculum reform of the Minas Gerais Federal University Technical College Electronics Technical Course. This reform followed the new guidelines that have regulated professional education since 1999. Pedagogical implications stemming from this model of competencies are discussed in relation to the assumptions of the Projects Method, evaluating its effectiveness and efficiency in the process of developing competencies. The article presents an account of a successful experience of applying this method and discusses its main results.